Educating Dental Students About Diet–Related Behavior Change: Does Experiential Learning Work?. Issue 1 (1st January 2014) - Taylor, George W.; Stumpos, Madelyn L.; Kerschbaum, Wendy; Inglehart, Marita Rohr
Abstract : The objective of this study was to explore whether an experiential exercise in a nutrition class would a) increase dental students' motivation to change their own diet–related behavior, b) improve their understanding of theoretical concepts related to behavior change, and c) improve their attitudes towards educating their patients about diet–related behavior. Data were collected from 218 senior dental students in one dental school (2010: 106; 2011: 112) during their nutrition class. The students agreed at the beginning that it was important to change their own diet–related behavior. After one week, the majority agreed that they had changed how they felt and thought about the targeted behavior and what they actually did. After three weeks and at the end of the term, they rated the exercise as helpful for gaining a better understanding of health education theories. The majority indicated that the exercise had helped them understand the difficulty of diet–related behavior change and that it had increased their interest in helping patients change their diet–related behavior. In conclusion, this study suggests that experiential learning about diet–related behavior change is likely to affect students' own behavior positively and to result in increased understanding of behavior change theories and positive behavioral intentions concerning future health education efforts with patients.